(Chemical Composition of Indonesian Traditional Food Additives Which Possibly Containing Borax) - Atih Surjati Herman; Renawati Iskandar; Binarti Dwi Astuti (Warta Industri Hasil Pertanian, 1991)
Five types of traditional food additives collacted from markets in Java and Manado, namely "bleng", "obat mi", "Pijer", "air abu/kansui" and "abu cina/kansai" were analysis for their chemical composition. The same chemical analysis was done to the solutions of straw ash and coconut shell ash, and also to natural mineral water ("bleng alam") collected from two sources in puwodadi/Central Java, which are traditionally used for food additives. Except "obat mi", the other four food additives contain boron. Composition of mineral water was different between the two sources, one contained boron while the other did not. Rough estimation composition of these additives are shown in the paper.